2015
DOI: 10.1038/srep10898
|View full text |Cite
|
Sign up to set email alerts
|

Meiosis completion and various sperm responses lead to unisexual and sexual reproduction modes in one clone of polyploid Carassius gibelio

Abstract: Unisexual polyploid vertebrates are commonly known to reproduce by gynogenesis, parthenogenesis, or hybridogenesis. One clone of polyploid Carassius gibelio has been revealed to possess multiple modes of unisexual gynogenesis and sexual reproduction, but the cytological and developmental mechanisms have remained unknown. In this study, normal meiosis completion was firstly confirmed by spindle co-localization of β-tubulin and Spindlin. Moreover, three types of various nuclear events and development behaviors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 58 publications
2
84
0
Order By: Relevance
“…These examined tissues include heart, liver, spleen, kidney, muscle, hypothalamus, pituitary, ovary, and testis. embryogenesis (Gui and Zhu, 2012), slbp2 has almost identical expression pattern with spindlin (Sun et al, 2010;Zhang et al, 2015) and histone H2A variant h2af1o (Wu et al, 2009) during oogenesis and oocyte maturation of C. gibelio. They exhibit the highest expression at cortical alveolus stage, and their mRNAs and proteins also show similar intracellular localization in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These examined tissues include heart, liver, spleen, kidney, muscle, hypothalamus, pituitary, ovary, and testis. embryogenesis (Gui and Zhu, 2012), slbp2 has almost identical expression pattern with spindlin (Sun et al, 2010;Zhang et al, 2015) and histone H2A variant h2af1o (Wu et al, 2009) during oogenesis and oocyte maturation of C. gibelio. They exhibit the highest expression at cortical alveolus stage, and their mRNAs and proteins also show similar intracellular localization in cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, however, no oocyte-specific SLBP have been characterized in fish. C. gibelio is a unique polyploid fish (Gui and Zhou, 2010;Jiang et al, 2013;Zhang et al, 2015) with dual reproduction modes of unisexual gynogenesis and sexual reproduction (Zhou et al, 2000;Mei and Gui, 2015). C. gibelio has become a promising model organism for understanding regulatory mechanisms of oocyte maturation, egg fertilization, and early embryogenesis (Gui and Zhou, 2010).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Chromosome numbers of gibel carp were detected to range from 135 to 162 (Cherfas, 1981;Tóth et al, 2000;Liasko et al, 2010;Zhou and Gui, 2002;Kalous and Knytl, 2011), and its gynogenetic reproduction mode was preliminarily observed early in the last century (Golovinskaya et al, 1965;Peňáz et al, 1979). Later, through artificial propagation experiments, cytological investigation and molecular marker analyses, its dual reproduction modes were revealed, in which unisexual gynogenesis is resulted from heterologous sperm of other species and sexual reproduction is performed by homologous sperm from the males of same gibel carp clones (Gui and Zhou, 2010;Mei and Gui, 2015;Zhang et al, 2015). And, ploidy evolution was also reported to be still in the evolutionary progress (Murayama et al, 1986;Gui et al, 1993a;Liasko et al, 2010;Gui and Zhou, 2010;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gibel carp, also commonly known Prussian carp, which was previously nominated as a subspecies (Carassius auratus gibelio) (Fan and Shen, 1990;Gui, 1997), has been recently suggested as a separate species Carassius gibelio (Rylkova et al, 2010;Gui and Zhou, 2010;Kalous and Knytl, 2011;Wang et al, 2011;Zhang et al, 2015). It has been found throughout a vast territory of Eurasian continent (Kottelat and Freyhof, 2007;Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike most unisexual vertebrates (Avise, 2008), gibel carp has been revealed to have multiple reproduction modes including unisexual gynogenesis and sexual reproduction (Zhou et al, 2000;Gui and Zhou, 2010;Li et al, 2014a;Mei and Gui, 2015;Zhang et al, 2015), and a high male incidence has been also observed in many natural populations (Jiang et al, 2013;Li et al, 2016). Utilizing it as an evolutional development biology model for screening reproduction-related genes, many important genes, such as oocytespecific and ovarian development-associated genes C-type lection (Dong et al, 2004), C1q-like (Mei et al, 2008(Mei et al, , 2014 and spindlin (Sun et al, 2010), oocyte-specific H2A variant h2af1o (Wu et al, 2009;Yue et al, 2013) and stem-loop binding protein-encoded gene slbp2 (Liu et al, 2015a), testis determination-related gene Dmrt1 (Li et al, 2014a), and germ cell marker genes Vasa and Dazl (Xu et al, 2005;Peng et al, 2009), have been identified and functionally characterized in gibel carp.…”
Section: Introductionmentioning
confidence: 99%